The Influence of Artificial Intelligence in the Resolution of Family Law Disputes: Prospects and Challenges - Yuliani, Sri; Firmansyah, Syarif; Prasetya, Raynaldi Nugraha (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This research aims to explore the prospects and challenges of applying Artificial Intelligence (AI) in family law dispute resolution. The method used in this research is a qualitative approach with literature study and normative juridical analysis, as well as interviews with legal practitioners and academics. The results show that AI has great potential in improving legal efficiency and accessibility by accelerating the mediation process and providing initial legal consultation for the community. However, the research also identified several key challenges, including AI's limitations in understanding the emotional and psychological aspects of family disputes, the risk of algorithm bias, and the legal validity of the resulting decisions. The implications of this research confirm that AI can be a useful support tool in the legal process, but it cannot completely replace the role of humans. Therefore, strict regulations as well as human involvement in the verification process and final decision-making are needed to ensure that justice is maintained.